Politik Hukum Masa Depan Pertanahan Indonesia - Muhammad Yamin Lubis (Recital Review, 2019)
Land issues in its development increasingly today continues to increase both in quantity and quality, this indicates that the interests of humans will land is not in line with the land area is steadily declining due to both natural disasters and transition designation that is constantly changing. Settings area of land, which is made yet to provide substantial protection against the subject, the object and the status of land rights that exist, so it is necessary agrarian reform can meminimalisisr conflicts and land disputes that occur.